Assessment of the relationship between follicular fluid calcium ion concentration and reproductive outcomes - Özdamar, Özkan; Gün, İsmet and Hira, Serdar and Devranoğlu, Belgin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Quantification of follicular fluid (FF) composition can provide valuable information about the oocyte state which can be helpful in distinguishing high and low quality oocyte. In the absence of appropriate calcium signaling at fertilization, the embryo may fail to implant and/or develop to full term. We herein aimed to investigate whether FF levels of Ca2+ ion concentrations vary between patients who achieved pregnancy and those who did not following a standard ICSI treatment regimen, and hence to determine whether FF Ca2+ levels could predict reproductive outcomes in patients undergoing ICSI. Methods: Patients seeking treatment for solely unexplained infertility were recruited in the period between June and December 2013 and were assigned to the groups according to their reproductive outcomes. Group 1 consisted of patients who conceived and Group 2 consisted of those who did not achieve pregnancy following ICSI. Parametric comparisons were performed using Student’s t-test. Categorical data were evaluated by using χ2 test. Results: Groups 1 and 2 consisted of 34 and 66 patients, respectively. Although FF Ca2+ ion concentrations were higher in those who did not achieve any pregnancy, the difference did not reached to statistical significance level (7.6±0.4 mg/dl and 7.9±0.9 mg/dl respectively, p=0.070). Conclusions: FF Ca2+ ion concentrations did not significantly differ between patients who achieved pregnancy and who did not followed ICSI attempts. Thus FF Ca2+ levels do not appear to be of benefit in predicting reproductive outcomes in unexplained infertility patients undergoing ICSI cycles.